KEPUASAN PENGGUNA GERBONG COMMUTERLINE KHUSUS WANITA - Naya Rahmauliya Syahputri; Fadila Fanifia, Hilmy Yaskur, Siti Sahara (CV. ADIBA AISHA AMIRA, 2023)
This publication aims to evaluate KRL Commuter Line passengers specifically for women. This research was conducted using a quantitative method by distributing questionnaires to female KRL Commuter Line passengers on the Jabodetabek route. This study shows that after the introduction of women-only carriages on all Commuter Line KRL Jabodetabek routes, the level of passenger satisfaction has increased. Especially during peak hours, respondents said they felt safer and more comfortable while commuting. However, some respondents also mentioned problems with seat addiction and a lack of attention to hygiene in the women-only carriages